Diversity in the Workplace: Benefits, Challenges, and the Required Managerial Tools - Kelli A. Green; Mayra López; Allen Wysocki; Karl Kepner (EDIS)
This is EDIS document HR 022, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002. It was designed to help managers effectively manage diverse workforces. It provides a general definition for workplace diversity, discusses the benefits and challenges of managing diverse workplaces, and presents effective strategies for managing diverse workforces.